Chambers Adult Learners' Guide to Spelling - Betteridge(3, (BAnnes (Rome chambers harrap, 2008)
Chambers Adult Learners' Guide to spelling is for all adults who lack confidence in their ability to spell. Packed with simple,jargon-free advice, itpresents strategies that can be used to learn any spelling for life
Practical methods for learning how to spell
12
Keywords: English Language; Spelling reform